Looking Back to Think Forward: What we Might Learn from Cold War Feminist Movements. (12th September 2022) - Engle, Karen
Abstract : The end of the Cold War wrought a shift in international legal priorities and preoccupations, including among feminists. When feminist approaches to international law, particularly to human rights and humanitarian law, began to make headway in the early 1990s, they had already left behind some of the anti-imperial and anti-military emphases of much of the internationally informed feminism of the 1970s and 80s. Here, I revisit some of those Cold War feminist approaches, with the hope of informing today's much-needed international legal attention to peace, disarmament—including nuclear disarmament—and global inequality.